2009
DOI: 10.1111/j.1398-9995.2009.02010.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum interleukin‐17 levels are related to clinical severity in allergic rhinitis

Abstract: This study provides evidence that serum IL-17 level assessment might be considered to classify allergy severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
112
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(120 citation statements)
references
References 17 publications
(19 reference statements)
6
112
2
Order By: Relevance
“…In addition, IL-17A may play a role in the development of various allergic diseases that have classically been considered to be Th2-mediated disorders (17). Moreover, IL-17A may be considered a new biomarker ofdisease progression and allergy severity as recently demonstrated in allergic rhinitis (8)(9). However, to date there have only been studies that investigated 11-17 at serum level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, IL-17A may play a role in the development of various allergic diseases that have classically been considered to be Th2-mediated disorders (17). Moreover, IL-17A may be considered a new biomarker ofdisease progression and allergy severity as recently demonstrated in allergic rhinitis (8)(9). However, to date there have only been studies that investigated 11-17 at serum level.…”
Section: Discussionmentioning
confidence: 99%
“…The skin prick test was performed according to the guidelines ofthe European Academy ofAllergy and Clinical Immunology (13), using a common panel as previously reported (8)(9).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Klemens et al (14) reported that IL-17 was detectable in the excretions of viral rhinitis patients and AR patients, but the IL-17 level in the viral rhinitis was dramatically higher than that in the AR patients. In addition, Ciprandi et al (15) found, in the pollen season, the serum level of IL-17 was closely relevant with the severity of clinical manifestations in patients with pollen induced AR. In the present study, our result revealed the serum level of IL-17 was markedly higher in AR patients than in healthy controls (P<0.05), which suggests IL-17 may play a crucial role in the pathogenesis of AR.…”
Section: Discussionmentioning
confidence: 99%
“…13,19,20 IL-17 has important roles in bridging innate and adaptive immunity, and is involved in the host defense against extracellular pathogens, the pathophysiology of autoimmune diseases, and allograft rejection of solid organs. [21][22][23][24][25][26][27][28][29] Moreover, several reports have so far shown that Th17 cells and IL-17 has a significant impact on the development of acute GVHD in mouse models. [30][31][32][33][34][35] Recent reports have shown association of SNPs in the IL-17 gene with autoimmune diseases such as rheumatoid arthritis and ulcerative colitis.…”
Section: Introductionmentioning
confidence: 99%